Odpowiedzi

Najlepsza Odpowiedź!
2009-12-09T16:58:47+01:00
1. 9x²-6xy+3x-6x+4y-2-6x²+12xy-4x=x²+6xy-7x+4y-2
2.3mn-6m+3n-6+2mn-4n+2m-4=5mn-4m-n-10
3.x³+2x²+x²+2x-x³+2x²+x²-2x=6x²+2x
1 5 1
2009-12-09T17:00:18+01:00
(3x - 2)(3x - 2y + 1) - 4x(2x - 3y +1)=9x-6xy+3x-6x-4y+2-8x²+12xy-4x=9x+3x-6x-4x-6xy+12xy-8x²=2x-18xy-8x²



3(m + 1)(n - 2) + 2(n + 1)(m - 2)=(3m+3)(n - 2)+(2n+2)(m - 2)=3mn+6m+3n-6+2mn-4n+2m-4=3mn+2mn+6m+2m+3n-4n-6-4=5mn+8m-n-2




x(x + 1)(x + 2) - x(x - 1)(x - 2)=(x²+x)(x+2)-(x²+x)(x - 2)=x³+2x²+x²+2x-x³+2x²+x²-2x=x³-x³+2x²+x²+2x²+x²+2x=6x²+2x
1 5 1